New bivalves to Peru in Independencia Bay - Cornejo, Oswaldo (2004)
The following species of marine bivalves have been recorded for the first time in Peru Nucula (Nucula) pisum Sowerby I,1833 and Lyonsia delicata Marincovich,1973, colected in Independencia Bay in Pisco, Peru, at 2002.